The Trouble with boys : social influences and the gender gap in disruptive behavior - Bertrand, Marianne (2013)
Explores the importance of the home and school environments in explaining the gender gap in disruptive behaviour. Documents large differences in the gender gap across key features of home environment - expecially in broken families.